Nepal’s COVID-19 Crisis: A Global Call to Arms - Maskey, Upasana; Sedhai, Yub Raj; Atreya, Alok; Kidwai, Aasim (Acta Biomedica Atenei Parmensis, 2021)
Nepal’s second wave of COVID-19 has become the worst the world has seen so far. For a population of 29 million people, Nepal currently has only 1127 ICU beds and 453 ventilators for the entire population. The fragile healthcare system is already overwhelmed with every emergency room full of patients. Due to the unavailability of ICU beds, ventilators, oxygen, and other vital resources, sick patients are forced to stay at home with home isolation and treatment. The situation is dire, and resources are saturated. Only humanitarian aid from foreign countries can help mitigate the unprecedented disaster.